Dysphagia in Parkinson's disease: Pharyngeal manometry and fiberoptic endoscopic evaluation. Issue 6 (December 2022) - Fattori, Bruno; Nacci, Andrea; Farneti, Daniele; Ceravolo, Roberto; Santoro, Amelia; Bastiani, Luca; Simoni, Federica; Pagani, Rebecca; De Bortoli, Nicola
Abstract: Objective: Dysphagia is a common symptom in Parkinson's disease (PD) and it represents a negative prognostic factor because of its complications. This study is to evaluate pharyngeal dysphagia for boluses of various consistencies with Fiberoptic Endoscopic Evaluation of Swallowing (FEES) and Pharyngeal High-Resolution Manometry (PHRM) in a group of PD patients, making a comparison between the information provided by the two exams. Methods: Group of 20 patients affected by PD was selected and initially subjected to a qualitative evaluation of the swallowing performing FEES. Subsequently, they were evaluated by PHRM to identify quantitative measures associated with pressures expressed by pharyngeal organs during swallowing. Values obtained in the study group were compared with those recorded in a group of 20 healthy subjects. Results: Study showed that Pmax (the maximum pressure elicited by the single pharyngeal muscle structures involved in swallowing) was significantly lower than the control group (p<0.05) for all the boluses and consistency tested, in particular for the Tongue base and the Cricopharyngeal muscle. Pmean pre-swallowing pressure (represents the mean value of a contraction in which basal and maximal pressure where normally calculated) was significantly higher compared to normal subjects for the Tongue base and the Cricopharyngeal muscle (p<0.05). Mean intra-swallowing pressure was higher for the Velopharynx and the Cricopharyngeal muscle, but lower for the tongue base. Pmax and Pmean at PHRM were altered independently to the degree of dysphagia detected at FEES, and they did not correlate either with the location of the residue or with the type of bolus. Images displayed at the FEES, found the corresponding biomechanical explanations in the PHRM, which also allowed us to quantify the extent of the dysfunction, through the calculation of the pressures generated in the various structures studied. Conclusion: PHRM is particularly useful in the early detection of dysphagia, when FEES may still show no evidence of abnormal swallowing.